Metabolic control analysis of respiration in human cancer tissue - Kaambre, Tuuli; Chekulayev, Vladimir; Shevchuk, Igor; Tepp, Kersti; Timohhina, Natalja; Varikmaa, Minna; Bagur, Rafaela; Klepinin, Aleksandr; Anmann, Tiia; Koit, Andre; Kaldma, Andrus; Guzun, Rita; et al. (Frontiers in Physiology, 2013)
Bioenergetic profiling of cancer cells is of great potential because it can bring forward new and effective therapeutic strategies along with early diagnosis. Metabolic Control Analysis (MCA) is a methodology that enables quantification of the flux control exerted by different enzymatic steps in a metabolic network thus assessing their contribution to the system`s function. Our main goal is to demonstrate the applicability of MCA for in situ studies of energy metabolism in human breast and colorectal cancer cells as well as in normal tissues. We seek to determine the metabolic conditions leading to energy flux redirection in cancer cells. A main result obtained is that the adenine nucleotide translocator exhibits the highest control of respiration in human breast cancer thus becoming a prospective therapeutic target. Additionally, we present evidence suggesting the existence of mitochondrial respiratory supercomplexes that may represent a way by which cancer cells avoid apoptosis. The data obtained show that MCA applied in situ can be insightful in cancer cell energetic research.